[1,5] and [1,2] acetyl shifts in Diels-Alder adducts of 2-acetyl-6-methyl-l,4-benzoquinone - Ahmad, Faujan; Bruce, J. Malcolm; Khalafy, Jabbar; Sabetian, Khojasteh (The Royal Society of Chemistry, 1981)
Treatment of the Diels-Alder adduct 4a-acetyl-4a, 5, 8, 8a-tetrahydro-3-methyl-I, 4 naphthoquinone with pyridine-methanol or acetic anhydride leads to a [I, 5J acetyl shift to the 3-position which can be followed by a [1,2J acetyl shift to the 2-position (adduct numbering).